SPORT MANAGEMENT THROUGH NATIONAL AND INTERNATIONAL SPORTS ORGANIZATIONS - (PhD),dos. S.A. Akhmedova; dos. S.N.Haydarov; N.O. Pirimova (American Journals, 2024)
In this created state, sports management is organized through national and international sports organizations. Upravlenie sistemoy sporta osnovyvaetsya na teorii upravleniya, menedzhmenta.
Keywords: Management, sport, administration